Diagnosis of urticaria - Nicole Schoepke; Georgios Doumoulakis; Marcus Maurer (Wolters Kluwer Medknow Publications, 2013)
Acute urticaria do not need extensive diagnostic procedures. Urticaria activity score is a useful tool for evaluation of urticaria. Complete blood count, Erythrocyte sedimentation rate and C reactive protein are important investigations for diagnosis of infections in urticaria. Autologous serum skin test is a simple office procedure for diagnosis of auto reactive urticaria. Closed ball point pen tip is a simple test to diagnose dermographism.